PCR reaction testing by using microsatellite DNA markers on Bali Myna samples (Leucopsar rothschildi Stressemann, 1912) - Utami Lestari Budiawati; Made Pharmawati; Luh Putu Eswaryanti Kusuma Yuni (Jurnal Biologi Udayana, 2025)
Genetic research requires a good quality and quantity of DNA template and appropriate conditions to obtain optimal PCR results. This study aimed to evaluate and compare PCR reaction conditions and compositions in Bali Myna (Leucopsar rothschildi Stressemann, 1912) samples in order to generate PCR products. Samples were obtained from calamus feathers and buccal swabs of captive Bali Mynas at Taman Nasional Bali Barat and the Friends of National Parks Foundation, Nusa Penida, Bali. The DNA extraction was carried out using Chelex® 5% and GeneJET Genomic DNA Purification Kit Thermo Fisher K0721. This study used microsatellite markers with five pairs primers (primer 1 Lr031337, primer 2 Lr052255, primer 3 Lr104861, primer 4 Lr123908, primer 5 Lr045800). The results indicated that calamus samples performed better than buccal swab samples. DNA extracted using the GeneJET Genomic DNA Purification Kit (Thermo Fisher K0721) yielded better results than DNA extracted using Chelex® 5%, as indicated by successful DNA amplification. PCR amplification using primer 3 was successfully achieved with a reaction mixture consisting of 10 µl (1×) mastermix, 1 µM forward primer, 1 µM reverse primer, and DNA template concentrations of 0.5 ng/µl, 1 ng/µl, 2.5 ng/µl, and 3.5 ng/µl. The PCR was performed at an annealing temperature of 55°C for 35 amplification cycles, producing a PCR product of 250 bp.